Clinical case of severe visceral complications with atypical localization in a patient with gout - Kuzmina, G.P.; Markova, O.Ya.; Lazarenko , O.M. (Medicni Perspektivi, 2023)
The diagnosed gout is a signal to search for unrecognized concomitant conditions and their underlying causes and mechanisms of development. Due to the fact that gout is a common metabolic disorder with symptoms of localized inflammation caused by chronic and/or episodic deposition of monosodium urate crystals (MSU) in joints and soft tissues, the understanding of the inflammation interaction in metabolic disorders has changed. In cases of severe visceral complications of gout, the most common sites of tophl are kidneys, liver, spleen, lungs, pericardium, subcutaneous tissue and other soft tissues. The aim of this study was to outline the features of severe visceral complications with atypical localization in a patient with gout (identification of MSU crystals with polarization microscopy) and to determine the role of videothoracoscopy in this case. Patient N., 55 years old, complained of moderate chest pain, shortness of breath during exercise, general weakness and occasional cough. The patient was hospitalized in a multidisciplinary clinical institution. Examinations were performed, including polarization microscopy, spiral computed tomography (polytopic foci, formations), videothoracoscopy. Endoscopic resection of SVII of the lower lobe of the left lung with a biopsy of the lungs formations and mediastinal lymph nodes was performed. Results of histologic examination: amorphous masses are presented in combination with the organized chronic giant cell granulomatous structure (tophus), which contains clusters of crystals of MSU. Cytological examination of pleural cavity fluid revealed the presence of crystals of MSU. The presence of crystals of MSU was confirmed by polarization microscopy. From the anamnesis of the disease it became known that at the age of 38 the patient consulted a rheumatologist for moderate joint syndrome. On the basis of anamnesis, laboratory and instrumental data (X-ray, ultrasound examination) the diagnosis of gout, chronic gouty arthritis was established. Urate lowering therapy was prescribed. The patient took the drugs periodically without re-consultation with the doctor. The presented case of untreated gout has led to significant structural disorders in organs such as lungs, pleura. Endoscopic resection of the lower lobe of the left lung and revision of the thoracic cavity revealed atelectasis, hemorrhage, inflammatory infiltration, fibrous changes in tissues, amorphous masses with organized chronic giant cell granulomatous structure, presented by crystals of MSU. During the surgery, a powdery substance was found on the pleura surfaces. A video thoracoscopy in this case was a means to present a visceral damage in gout. The search for diagnostic tools to diagnose a severe visceral complications with atypical localization in gout still remains unsolved. Undoubtedly, the central role in the development of gout is played by the deposition of numerous crystals of MSU. In the patient under observation, crystals of MSU were found in pleural fluid and sputum consisting of sodium urate, like the known facts of their appearance in the joint fluid and urine. Uric acid salt crystals were also detected in the areas of pulmonary fibrosis formation according to the results of radiological examination, as well as endoscopic intervention in the lower lobe of the left lung.